Thermal performance in solar air heater channel with combined wavy-groove and perforated-delta wing vortex generators - Skullong, Sompol; Promvonge, Pongjet; Thianpong, Chinaruk; Pimsarn, Monsak (My University, 2016)
An experimental investigation on thermal performance improvement in a solar air heater channel with combined wavy-groove and delta-wing vortex generator (WVG) placed on the absorber plate having a uniform wall heat-flux is carried out. The Reynolds number based on the hydraulic diameter of the channel ranges from 4800 to 23,000. The effect of the combined groove and WVG on the heat transfer and pressure drop in the channel in terms of respective Nusselt number and friction factor is examined. Investigated parameters of the WVG mounted on the grooved absorber are three wing porosity area ratios (called porosity ratio, Ah/Aw = 0.031, 0.085 and 0.167) and four groove-wing distance to channel-height ratios (g/H = 0.4, 0.5, 0.75 and 1) at a single attack angle (α = 45°). The experimental result reveals that at g/H = 0.5, the smaller Ah/Aw provides the highest Nusselt number and friction factor around 6 and 30 times over the smooth channel, respectively, but the optimum thermal performance is at Ah/Aw = 0.085 and g/H = 0.5. The combined devices give the thermal performance augmentation at about 37.7-46.3% higher than the groove alone and also at about 1.5-12.5% above the combined groove and non-perforated WVG (without hole).
Keywords: Delta-wing; Solar air heater; Thermal performance; Vortex generators; Wavy-groove